Evaluation of concentrate feeding strategies in an intensive grass silage-based dairy production system - Kajava, Sari; Sairanen, Auvo; Rinne, Marketta (Elsevier, 2026)
Environmental and societal pressures are encouraging to reduce the proportion of concentrate feeds in grass-based dairy production systems. The objective of this experiment was to compare two concentrate feeding strategies to reduce the concentrate use in dairy cow diets: 1) a constant concentrate proportion of 35 % throughout the lactation period, and 2) an adjusted strategy with 45 % in early lactation (EL) and 25 % in late lactation (LL). The strategies were simulated in two separate and parallel 8-week sub-experiments for EL and LL, each including a common concentrate level of 35 %. In EL, the comparison was made against 45 %, and in LL against 25 %. The strategies were indirectly compared based on production responses. Sub-experiments were conducted with 20 multiparous Nordic Red cows per lactation stage. Higher concentrate in EL (EL-45) increased energy-corrected milk, fat and protein yields compared to EL-35, with no significant differences in body weight change, energy balance or plasma BHBA and NEFA concentrations. The production response to concentrate supplementation was greater in EL than LL (1.3 and 0.9 kg ECM per kg additional concentrate, respectively). In LL, feed efficiency was higher, and body weight gain was lower with the lower concentrate diet. These findings suggest that under current feed prices, prioritising concentrate use in early lactation and reducing it in late lactation is more cost-effective and helps limit excessive body weight gain in late lactation.
Keywords: dairy cow; energy balance; feed efficiency; forage proportion; early lactation; late lactation